Combined Effects of Metformin, Quercetin, and Fractionated Gamma Irradiation on MiR-107-Mediated Brain Injury in HFD/STZ-Induced Diabetic Rats - Omayma A. R. Abozaid; Fatma S. M. Moawed; Hanaa F. B. Gabr; Marwa A. Esmat (Dose-Response)
Objectives: MiR-107 upregulation represents a key target among the multiple pathways associated with T2DM. Given that drug combinations offer significant therapeutic potential, this study investigated the antidiabetic, antioxidant, and anti-inflammatory effects of γ-irradiation, the quercetin (common flavonol), and the metformin (biguanide) on HFD/STZ-induced diabetic rats’ brains. Methods: Diabetic rats were treated with metformin (200 mg/kg b.w./day) alone or in combination with quercetin (30 mg/kg b.w./day) and/or γ-radiation (fractionated 4 Gy) for 4 weeks. Results: The diabetic group exhibited increased body weight, blood glucose, HOMA-IR, AChE, MMP-2, and lipid peroxidation, while serum insulin and brain GPx antioxidant enzyme activity were significantly decreased. Similarly, BDNF and SIRTI transcript levels and IRS1 protein expression were reduced, whereas NF-κB and MiR-107 transcript levels were elevated in diabetic rats compared to controls. Histopathological examination of diabetic brain tissue corroborated the biochemical findings. Treatment with metformin alone or in combination with γ-irradiation and/or quercetin effectively mitigated these effects by downregulating miR-107 and improving brain function, with optimal results achieved through combined therapy. Conclusion: The synergistic combination of Metformin, fractionated gamma-irradiation, and quercetin effectively attenuates brain injury in diabetic rats by enhancing IRS1/SIRT1/BDNF signaling while suppressing MiR-107/NF-κB pathways.